Perceived tenure (in)security in the era of rural transformation: Gender-disaggregated analysis from Mozambique - Ghebru, Hosaena; Girmachew, Fikirte (International Food Policy Research Institute, 2019)
This study examines the drivers of tenure insecurity in Mozambique using data from the National Agricultural Survey (TIA) 2014 as well as a follow-up supplemental survey with detailed land tenure gender-disaggregated data from three groups: namely, principal male, principal female, and female spouses. Perceived risk of land loss (collective tenure risk) and perceived risk of a private land dispute (individual tenure risk) are used to measure land tenure insecurity. The empirical findings reveal, overall, collective tenure risks are the real threat to women’s tenure security while individual tenure risks (ownership, inheritance, border disputes, etc.) are more of a threat to the tenure security of men. However, a more gender-disaggregated analysis reveals that individual tenure risk is higher among female spouses as compared to male heads within the same household. Moreover, perceived risk of land loss is higher among non-indigenous male heads while female spouses who have no control over family land are more likely to have higher perceived tenure insecurity. Results also show that land-related legal awareness seems to be more significant in dictating the (positively) perceived tenure security of women as compared to their male counterparts. Generally, tenure insecurity for female spouses seem to be associated with the emergence of land markets while relative land scarcity in a given community dictates tenure insecurity of the principal female (female heads). Hence, the empirical findings reinforce the need to complement ongoing efforts to enhance tenure security at the household and community level with gender-tailored/targeted programs that take into account the intra-household dimension of addressing issues of land tenure security.